A glimpse of things to come: OSHA's soon to be updated hazard communication standard. Issue 2 (9th January 2019) - Bergeson, Lynn L.
Abstract: In the Trump Administration's Unified Agenda of Regulatory and Deregulatory Actions (Regulatory Agenda) issued on October 17, 2018, the US Department of Labor's Occupational Safety and Health Administration (OSHA) published a Proposed Rule Stage item titled, "Update to the Hazard Communication Standard, " RIN 1218‐AC93 (OSHA, 2018 ), and scheduled the Notice of Proposed Rulemaking (NPRM) to be issued by March 2019. This could be an important regulatory development for all entities subject to Hazard Communication Standard (HCS) requirements, which is just about everyone. This column explains why this development is significant.